1998
DOI: 10.1159/000008558
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies against Cardiolipin in the Serum of Patients with Colorectal Adenocarcinoma:Their Prognostic Significance

Abstract: Using an ELISA method, the sera of 43 patients with colon adenocarcinoma (CA) and of 26 surgical patients with nonmalignant disease of the gastrointestinal tract were studied for the presence of autoantibodies against cardiolipin (CLP) before and 1 month after surgery. Forty healthy volunteers were used as controls. Fourteen CA patients were found to be positive for anti-CLP autoantibodies before surgical treatment, and 15 patients were found to be positive 1 month after surgery. The difference between the gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…A total of 235 patients with GI cancer were evaluated in 5 studies; patients were 5.1 times more likely than controls to develop aCL antibodies (95% CI, 2.6-9.95) (Table 1). [26][27][28][29][30] Two studies included patients with GU cancer (n 5 49) with increased pooled risk of developing aCL antibodies compared with healthy controls (RR, 7.3; 95% CI, 3.3-16.2). 30,31 Pooled risk estimates from 2 studies evaluating 62 patients with breast cancer were not statistically significant (RR, 1.9; 95% CI, 0.19-19.9).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 235 patients with GI cancer were evaluated in 5 studies; patients were 5.1 times more likely than controls to develop aCL antibodies (95% CI, 2.6-9.95) (Table 1). [26][27][28][29][30] Two studies included patients with GU cancer (n 5 49) with increased pooled risk of developing aCL antibodies compared with healthy controls (RR, 7.3; 95% CI, 3.3-16.2). 30,31 Pooled risk estimates from 2 studies evaluating 62 patients with breast cancer were not statistically significant (RR, 1.9; 95% CI, 0.19-19.9).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…For this analysis, we included the prevalence of antibodies for all studies, with or without controls (Table 2). The pooled prevalence rates of the various types of cancer ranged between 7% and 28% for aCL antibodies, 19,[24][25][26][27][28][29][30][31][32][40][41][42][43][44][45][46][47][48][49][50] between 5% and 53% for anti-b2-GPI antibodies, [24][25][26]33,40,42,44,45,51,52 and from 3% to 80% for LA. [23][24][25]32,45,49,50,53,54 Two studies examined all 3 aPL antibodies, but none of them reported the percentage of patients who were positive for all 3; therefore, the pooled prevalence rate of triplepositive aPL antibodies could not be determined.…”
Section: Pooled Prevalence Rates Of Developing Apl Antibodies In Patients With Solid Tumors (31 Studies)mentioning
confidence: 99%
“…We also collected multiple autoantibodies in 42 different combinations for CRC (Table 2). 11-83 The research was mainly undertaken in China (n = 20) and the USA (n = 12), with the remainder in Japan, Germany, Spain, and elsewher...…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the reference lists of review articles and related articles were manually screened to identify additional studies. Finally, a total of 80 articles involving 145 specific tumour‐associated autoantibodies detected in patients with CRC were selected (Table ) . Anti‐p53 antibody was the most commonly studied autoantibody, followed by MUC1, CEA, c‐myc, survivin, HDAC5, p62, ANXA4, koc, NY‐CO‐16, NY‐ESO‐1, RPH3AL, cyclin B, Imp1, IMPDH2 and MAGEA3.…”
Section: Resultsmentioning
confidence: 99%